Compatibility studies on development of pearl millet flour based pasta - Gull, Amir; Muzaffar, Khalid; Nayik, Gulzar Ahmad; Ganaie, Tariq Ahmad; Kumar, Pradyuman (Journal of Postharvest Technology, 2017)
Convenience and palatability make the pasta more popular worldwide and very recently it is gaining popularity among the common man in India too. This traditional cereal based food is a result of dough or moisture enriched flour, shaped in various forms. Spaghetti, macaroni and vermicelli are the popular pasta forms. Normally, this product is high in starch but low in dietary fiber, minerals, vitamins and phenolic compounds. Increased concern for health consciousness, nutritious pasta products richin fibre and various essential micronutrients having low glycemic index may be of preference. Pearl millet is an extensively grown tiny millet grain and found rich in dietary fibre and essential minerals. High polyphenol content of seed coat gives this millet a dark brown tinge. Addition of pearl millet flour to semolina in making the pasta not only improves the nutritional properties but also found an attractive colour and thus affected the appearance. The extent of tinge may thus be considered as an indicator of pearl millet addition and reflects the nutritional enhancement. Physical, chemical, cooking rheological and sensory evaluation was carried out for the developed pasta and found the optimal cooking time lesser than control pasta with softer texture. Therefore, quality pasta by substituting semolina with pearl millet flour could be developed, which not only enrich the pasta with various phytochemicals but also give variety to the range of pasta and options to use the millet in value addition.